PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PENINGKATAN PEMBELAJARAN BANGUN RUANG SISWA KELAS V SD NEGERI 2 PEJAGATAN TAHUN AJARAN 2013/2014. - MARWANTO, RUDY (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract:Application Contextual Teaching And Learning (CTL ) Model in Increasing Geometry Learning at the Fiveth Grade Students of State Elementary School 2 Pejagatan in Academic Year 2013/2014. The objectives of this research is to describe the right steps on application of contextual teaching and learning model in increasing geometry learning at the fifth grade students and to examine capability of contextual teaching and learning model in increasing geometry learning at the fifth grade students of state elementary school 2 Pejagatan in academic year 2013/2014. This research is a collaborative Classroom Action Research (CAR). This research was conducted in two cycles, with three meetings on each cycle. Each cycle consists of planning, observation, implementation and reflection. Subjects were fifth grade students of state elementary school 2 Pejagatan totaling 20 student. Data sources were from observers, students and teachers. Data collection techniques were observations, interview, tests and documents. Validity of data used triangulation techniques and data sources. Conclusion of this research is application of contextual teaching and learning model can increasing geometry learning at the fifth grade students of state elementary school 2 Pejagatan in academic year 2013/2014. Keywords: contextual teaching and learning, geometry Abstract: Penerapan Model Contextual Teaching And Learning (CTL) dalam Peningkatan Pembelajaran Bangun Ruang Siswa Kelas V SD Negeri 2 Pejagatan  Tahun Ajaran 2013/2014. Tujuan penelitian ini adalah mendeskripsikan bentuk penerapan model pembelajaran CTL dalam peningkatan pembelajaran Matematika tentang bangun ruang pada siswa kelas V dan meningkatkan pembelajran Matematika tentang bangun ruang pada siswa kelas V SDN 2 Pejagatan tahun ajaran 2013/2014. Penelitian ini merupakan PTK kolaboratif, yang dilaksanakan dalam 2 siklus, dengan 6 kali pertemuan. Tiap siklus terdiri atas perencanaan, pengamatan, pelaksanaan, dan refleksi. Subjek penelitian adalah siswa kelas V SD Negeri 2 Pejagatan berjumlah 20 siswa. Sumber data dari observer, siswa kelas V SD, dan guru kelas V SD. Teknik pengumpulan data dengan observasi, wawancara, tes, dan dokumen. Validitas data menggunakan triangulasi teknik dan triagulasi sumber data. Simpulan penelitian ini adalah penggunaan model CTL dapat meningkatan pembelajaran bangun ruang siswa kelas V SD Negeri 2 Pejagatan tahun ajaran 2013/2014. Kata kunci: Contextual Teaching And Learning, bangun ruang